Addressing gender in energy studies. (July 2020) - Fathallah, Judith; Pyakurel, Parakram
Abstract: Although there are several studies on energy and gender, most of the studies have conflated 'sex' and 'gender' and there are some inconsistent and imprecise uses of these terms in energy and gender studies. In this article, we explore some differences between 'sex' and 'gender' from a Global North perspective based on current gender theory that can be helpful to ensure that these terms are used more consistently and precisely when conducting energy and gender studies. We contend that most of the existing gender and energy studies are often inadequate in that they only address energy and a biological conception of sex, or else simplistically equate gender with a masculine/feminine binary that may actually reinforce essentializing gender myths. Thus, we highlight an important gap in energy and gender research and propose a conceptual approach to precisely and consistently utilize the terms 'sex' and 'energy'. Furthermore, we emphasize the need of considering gender impacts while devising energy policies and set out research agenda to make energy and gender studies more rigorous. This study is focused on the Global North, and similar studies are also needed for Global South.